2020
DOI: 10.1111/pin.12888
|View full text |Cite
|
Sign up to set email alerts
|

Syncytial variant of classic Hodgkin lymphoma: Four cases diagnosed with the aid of CD274/programmed cell death ligand 1 immunohistochemistry

Abstract: Although several reports have highlighted neoplastic PD‐L1 (nPD‐L1) expression in classic Hodgkin lymphoma (CHL), some have addressed associations between its expression and detailed histopathologic features. Here we describe four cases of syncytial variant of CHL (SV‐CHL), with and without Epstein–Barr virus (EBV) association, and highlight the diagnostic utility of PD‐L1 (clone SP142) immunohistochemistry. The patients were a 61‐year‐old male, 45‐year‐old male, 85‐year‐old female, and 89‐year‐old female. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, although the association of HS with other lymphocytic leukemia/lymphomas had been frequently reported in recent years, most of which still presented as the noncohesive or single diffuse proliferation cells in biopsy [9][10][11]. The atypical cohesive growth pattern of large neoplastic cells only appeared in several cases of B-cell lymphomas of plasma blastic lymphoma (PBL) [12,13], T-cell lymphomas of anaplastic large cell lymphoma (ALCL) [14,15], other metastatic carcinoma to bone marrow [16] and one case of classic Hodgkin lymphoma (CHL) [17]. Interestingly, in this case, a rare sight that neoplastic cell in tightness cohesive clusters with symplasm morphological was distinctly observed on this bone marrow smear, even accompanying with the hemophagocytosis and EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although the association of HS with other lymphocytic leukemia/lymphomas had been frequently reported in recent years, most of which still presented as the noncohesive or single diffuse proliferation cells in biopsy [9][10][11]. The atypical cohesive growth pattern of large neoplastic cells only appeared in several cases of B-cell lymphomas of plasma blastic lymphoma (PBL) [12,13], T-cell lymphomas of anaplastic large cell lymphoma (ALCL) [14,15], other metastatic carcinoma to bone marrow [16] and one case of classic Hodgkin lymphoma (CHL) [17]. Interestingly, in this case, a rare sight that neoplastic cell in tightness cohesive clusters with symplasm morphological was distinctly observed on this bone marrow smear, even accompanying with the hemophagocytosis and EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the presence of HRS cells is seemingly associated with PD-L1 expression, especially in EBV − CHLs. In the syncytial variant, PD-L1 expression is primarily found in HRS cells, but also rarely in small cohesive tumor cells [ 166 ]. It is currently unclear whether this heterogeneity is derived from genetic heterogeneity or transient expression induced by intracellular signaling, such as JAK/STAT activation.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Compared with positivity on HRS cells in typical areas of CHL, the difference suggests downregulation of nPD-L1 expression with the histopathological progression of CHL. 19 Hollander et al also reported the decreased expression of PD-L1 in HRS cells in consecutive biopsies of a small subset (10-18%) of CHL cases regardless of the treatment setting, but there was no reference of their histopathological findings. 20 MCCHL usually lacks nodular sclerosis and lacunar cells, although fine interstitial fibrosis may be observed.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%